Nanoparticle Saltwater Fish Powder and Cell Protein Pathways in Enamel Density Enhancement - Christiono, Sandy; Hutami, Islamy Rahma; Latief, Fourier Dzar Eljabbar; Rochmah, Yayun Siti; Aditya, Grahita; Suparmi, Suparmi; Afroz, Shaista; Yuniar, Savira Nurazky (European Journal of Dentistry, 2025)
This study aims to evaluate the effect of nanoparticle saltwater fish powder on amelogenin expression and FABP-3 levels in fetal mice, with the goal of enhancing enamel density and supporting tooth mineralization. To date, this relationship has not been clearly explained in previous studies.This randomized experimental study involved 16 pregnant mice, divided into two groups: control and treatment. The treatment group received nanoparticle saltwater fish powder (2.14 mg/mL) orally three times daily, while the control group received distilled water. On gestational day 18, placental and fetal jaw tissues were collected. Amelogenin and FABP-3 expressions were analyzed by immunohistochemistry (IHC), while enamel density was assessed using micro-computed tomography (µCT).Data were analyzed using SPSS 26 and presented as mean ± SD. Group differences were tested using an independent t-test; results were considered significant at p < 0.05.IHC analysis revealed significantly increased amelogenin expression in the treatment group receiving nanoparticle saltwater fish powder (4.34 ± 3.26) compared to the control group (0.49 ± 0.40), with a p-value of 0.005. FABP-3 expression was also significantly higher in the treatment group (2.26 ± 0.85) than in the control (1.50 ± 0.40), with a p-value of 0.038. µCT imaging displayed differences in enamel density between the treatment group (228.73 ± 5.31) versus the control (220.75 ± 5.95), with a p-value of 0.022.Nanoparticle saltwater fish powder modulates amelogenin expression during enamel secretion and enhances FABP-3 expression, suggesting potential benefits for promoting enamel development through nutritional interventions. Moreover, µCT analysis revealed an increase in the mean enamel density.
Keywords: amelogenin; FABP-3; fetal mice; enamel density; nanoparticle; saltwater fish powder